Glycosylated-imidazole aldoximes as reactivators of pesticides inhibited AChE: Synthesis and in-vitro reactivation study - Sharma, Rahul; Upadhyaya, Kapil; Gupta, Bhanushree; Ghosh, Kallol K; Tripathi, Rama P; Musilek, Kamil; Kuca, Kamil (Environmental toxicology and pharmacology, 2020)
The present armamentarium of commercially available antidotes provides limited protection against the neurological effects of organophosphate exposure. Hence, there is an urgent need to design and develop molecules that can protect and reactivate inhibited-AChE in the central nervous system. Some natural compounds like glucose and certain amino acids (glutamate, the anion of glutamic acid) can easily cross the blood brain barrier although they are highly polar. Glucose is mainly transported by systems like glucose transporter protein type 1 (GLUT1). For this reason, a series of non-quaternary and quaternary glycosylated imidazolium oximes with different alkane linkers have been designed and synthesized. These compounds were evaluated for their in-vitro reactivation ability against pesticide (paraoxon-ethyl and paraoxon-methyl) inhibited-AChE and compared with standards antidote AChE reactivators pralidoxime and obidoxime. Several physicochemical properties including acid dissociation constant (pKa), logP, logD, HBD and HBA, have also been assessed for reported compounds. Out of the synthesized compounds, three have exhibited comparable potency with a standard antidote (pralidoxime).
Keywords: kinetika; Reactivation; Acetylcholinesterase; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; Physico-chemical properties; Glycosylated-imidazole aldoximes; Cholinesterase Inhibitors; Pesticides; Oximes; zvířata; imidazoly; Kinetics; molekulární struktura; Electrophorus; pesticidy; oximy; reaktivátory cholinesterasy; Imidazoles; Molecular Structure; Animals